Medium optimization for submerged fermentative production of β‐cyclodextrin glucosyltransferase by isolated novel alkalihalophilic Bacillus sp. NCIM 5799 using statistical approach. (5th June 2022) - Solanki, P.; Banerjee, T.
Abstract: β‐cyclodextrin glucosyltransferase (β‐CGTase) is an essential enzyme to catalyse the biotransformation of starch into β‐cyclodextrins (β‐CD). β‐CD has widespread applications in the biomedical, pharmaceutical and food industries. The present study focused on β‐CGTase production using an efficient natural microbial strain and statistical production optimization for enhanced production. The isolated organism Bacillus sp. NCIM 5799 was found to be 5 μm short bacilli under FE‐SEM and alkalihalophilic in nature. The β‐CGTase production was optimized using a combination of Plackett–Burman design (PBD) and Central Composite Design—Response Surface Methodology (CCD‐RSM). On PBD screening Na2 CO3, peptone and MgSO4 .7H2 O were found to be significant for optimal β‐CGTase production, whereas the soluble starch and K2 HPO4 concentrations were found to be nonsignificant for β‐CGTase production. The significant factors obtained after PBD were further optimized using CCD‐RSM design. Peptone was found to have a significant interaction effect with Na2 CO3, and MgSO4 ·7H2 O and Na2 CO3 exhibited a significant effect on the production of CGTase. The production of β‐CGTase was enhanced in the presence of peptone (3%) and Na2 CO3 (0·8%). CGTase production obtained was 156·76 U/ml when optimized using CCD‐RSM. The final optimized medium (RSM) shows 7·7‐ and 5·4‐fold high productions as compared to un‐optimized and one factor at a time production media. Abstract : Significance and Impact of the Study: The novel isolated alkalihalophilic Bacillus sp. NCIM 5799 is a predominant producer of β‐cyclodextrin glucosyltransferase (β‐CGTase). This was the first report that the production of β‐CGTase was enhanced by applying two statistical approaches that are PBD and CCD‐RSM. The novel isolated Bacillus sp. NCIM 5799 could be utilized for industrial production of β‐CGTase.